The effectiveness of galactomyces ferment filtrate, dexpanthenol and Centella asiatica combination serum in the treatment of post-acne hyperpigmentation - We Sagara Dewi; Ivan Kurniadi; Anis Irawan Anwar (DiscoverSys Inc, 2020)
Background: Acne vulgaris is a chronic inflammation of the pilosebaceous gland that may result in both non-inflammatory and inflammatory lesions. Post-acne hyperpigmentation (PAH) is caused by a hypermelanotic reaction to skin inflammation. It can occur secondary to the inflammation process and depending on the severity, may persist for a prolonged period.Objective To determine the effectiveness of galactomyces ferment filtrate (GFF), dexpanthenol, and Centella asiatica combination serum in the treatment of PAHMethods: This was a placebo-controlled randomized clinical trial. There are 68 subjectsÂ that were divided into two groups: the experimental group received combination serum while the control group received placebo for 8 weeks. Three drops of serum were applied to the area with PAH twice daily in the morning and at night. The melanin, erythema, roughness, and L*, a*, and b* scores were assessed objectively using mexameter, chromameter and skin analyzer for every two weeks. Pearsonâ€™s correlation test and independent T-test were used to assess the trend of the parameters and compare the results of both groups.Results: The results of statistical calculations using Pearson correlation test showed the treatment group showed a significant decreasing trend of the melanin and spots score. Both groups showed significant decreasing trend in erythema, L* score and roughness. However, no significant difference was found between both groups in all parameters.Conclusion: The combination serum may decrease the melanin and spot scores suggesting that it affects the melanocyte activity. It has shown a good efficacy in treating PAH.